Application of three-dimensional flower-like nanomaterials in the fabrication of sandwich-type electrochemical immunosensors. Issue 107 (19th October 2015) - Wang, Yulan; Li, Yan; Hu, Lihua; Ren, Xiang; Du, Bin; Ma, Hongmin; Wei, Qin
Abstract : A novel and ultrasensitive sandwich-type electrochemical immunosensor was developed for the quantitative detection of carcinoembryonic antigen (CEA) in this work. Abstract : A novel and ultrasensitive sandwich-type electrochemical immunosensor was developed for the quantitative detection of carcinoembryonic antigen (CEA) in this work. Three-dimensional (3D) ZnO nanoflowers (NFs) were 3-aminopropyl-functionalized as the matrix to immobilize the primary antibodies (Ab1 ). The unique 3D flower-like nanostructure of ZnO provided a higher surface area for the capture of proteins. 3D AuPd NFs were employed as the label to immobilize the secondary antibodies (Ab2 ). The unique 3D flower-like nanostructure of AuPd produced a better electrocatalytic performance towards the reduction of hydrogen peroxide (H2 O2 ). Due to the special electrochemical performance of 3D flower-like nanomaterials, the facile and sensitive fabrication of the designed immunosensor was achieved. Under optimal conditions, the designed immunosensor exhibited a wide linear range from 10 −5 ng mL −1 to 10 2 ng mL −1 with a low detection limit of 3.2 fg mL −1 for CEA. It also displayed an electrochemical performance with good reproducibility, selectivity and stability, which would provide potential applications in the clinical diagnosis of other tumor markers.